RHIZOCTONIA BINUKLEAT HIPOVIRULEN SEBAGAI AGENS PENGENDALI HAYATI PENYAKIT REBAH SEMAI (Rhizoctonia solani) TUSAM (Pinus merkusii) DAN PENGARUHNYA TERHADAP EKTOMIKORIZA - , Rosa Suryantini, S.Hut.,MP.; , Prof. Dr. Ir. Achmadi Priyatmojo, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Tusam increased demand is the reason of the tusam cropping development in hutan tanam industri (HTI). Consequently tusam seedling demand with good quantity and quality increase but the development of damping off became problems in the development of tusam HTI. One of biocontrol of disease is the use of biocontrol agent as HBNR (hypovirulent binucleate Rhizoctonia). HBNR has been used on annual crops but has not ever been studied in forestry crops (especially tusam), so the aims of this research were to learn HBNRâs potential in inhibiting the growth of R. solani in vitro, growth pattern of HBNR and R. solani on tusam roots, HBNR effectiveness as biocontrol agent of damping off on tusam seedling and HBNR affects on ectomycorrhizae. Rhizoctonia as biocontrol agent was isolated from tusam stands soil in Bogor, Slemann and Jember. R. solani was isolated from tusam seedling roots. Ectomycorrhizal fungi was taken from under tusam stands. Characterizations were performed on Rhizoctonia spp., R. solani and ectomycorrhizal fungi, and hypovirulence tests of Rhizoctonia spp. Inhibition of R. solani was evaluated with antagonistic test of HBNR in vitro. HBNR and R. solani were inoculated on tusam seedling roots to study their growth pattern in seedling roots. Ectomycorrhizal fungi, HBNR and R. solani were inoculated in growth medium that had been planted with tusam seedlings. The results of this research showed that colony colour of Rhizoctonia spp. were white and tan to dark brown, and binucleate. R. solani was multinucleate and able to cause seedling death at age 15 and 30 days. Based on its characteristic, ectomycorrhizal fungi which grown under tusam stands was Lactarius sp. Optimum temperature of vegetative growth rate of binucleate Rhizoctonia spp., R. solani and Lactarius sp. were 25,21 Ì¶ 27,04 oC. From 5 binucleate Rhizoctonia spp. isolates, only Rhizoctonia sp. 2 that was hypovirulent on tusam, cucumber, tomato, corn and chili seedlings (selected HBNR). HBNR inhibited R. solani at average of 9,58 % on the 4th day in vitro. Growth inhibition R. solani was caused by competition and not due to mycoparasitism activity. HBNR did not form infection cushion on site infection whereas R. solani did it. HBNR that were inoculated 9 and 14 days after seedlings planted, reduced seedlings mortality from 97,87 % (control) to 5 % and 11,38 %. HBNR that was inoculated 14 days after seedlings planted in mycorrhizal medium and inoculated R. solani also reduced the number of seedlings mortality (7,30 %). But on HBNR that was inoculated 9 days after seedlings planted in mycorrhizal medium and inoculated R. solani, the number of seedling mortality (47,86 %) were greater than seedlings that were only R. solani in mycorrhizal medium (28,87 %). R. solani inhibition by HBNR was also caused by phenol compound increasing and callose deposition. HBNR did not effect significantly on ectomycorrhizal, shoot height, seedlings root-shoot ratios but increased root-shoot ratio (2,26) when HBNR was inoculated 14 days after seedlings planted in mycorrhizal medium, so it had fulfilled one of the conditions of seedling to be planted in the field.